Public health impact and cost-effectiveness of catch-up 9-valent HPV vaccination of individuals through age 45 years in the United States - Daniels, Vincent (Hum Vaccin Immunother, 2021)
The Advisory Committee on Immunization Practices (ACIP) recommended catch-up 9-valent Human Papillomavirus (HPV) vaccination through age 26 years, and shared clinical decision-making for adults aged 27–45 years, compared with catch-up through age 26 years and 21 years for females and males, respectively (status quo; pre-June-2019 recommendations). This study assessed the public health impact and cost-effectiveness of expanded catch-up vaccination through age 45 years (expanded catch-up) compared with status quo. We used an HPV dynamic transmission infection and disease model to assess disease outcomes and incremental cost-effectiveness ratio (ICER) of expanded catch-up compared with status quo. Costs (2018 USD), calculated from a healthcare sector perspective, and quality-adjusted life years (QALY) were discounted at 3% annually. Historical vaccination coverage was estimated using NIS-TEEN survey data (NHANES data for sensitivity analysis). Alternative scenario analyses included restricting upper age of expanded catch-up through 26 years (June-2019 ACIP recommendation), 29 years, and further 5-year increments. Our results show expanded catch-up vaccination would prevent additional 37,856 cancers, 314,468 cervical intraepithelial neoplasia-2/3s, 1,743,461 genital warts, and 10,698 deaths compared with status quo over 100 years at cost of $141,000/QALY. With NHANES coverage, the ICER was $96,000/QALY. The June-2019 ACIP recommendation also provided public health benefits with an ICER of $117,000/QALY, compared with status quo. The ICER for expanded vaccination through age 34 years was $107,000/QALY. Expanding catch-up vaccination program through age 45 years-old in the US is expected to provide public health benefits, and cost-effectiveness improves with expanding catch-up through age 34.